Kreativitas Guru dan Kemampuan Mengelola Kelas terhadap Pendidikan Agama Islam - Aminuddin Aminuddin; Wedra Aprison (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2021)
The teacher is one of the extrinsic factors that can have an influence on student learning outcomes. A teacher who has high creativity and is able to manage the class properly and correctly with the aim of creating and maintaining a classroom atmosphere, supporting teaching programs to improve student learning outcomes. This research is motivated because of several phenomena in the field, namely in the implementation of learning PAI in the classroom, it is known that the way the teacher presents material to students is still classified as less varied, this is indicated by the existence of less attractive learning media provided by the teacher so that there are students who plays during the learning process. Teachers have not applied various methods in learning so that learning is less interesting. This study aims 1) to determine the effect of teacher creativity on student learning outcomes in the field of PAI, 2) to determine the effect of classroom management on stu dent learning outcomes in the field of PAI, 3) To determine how much influence teacher creativity and the ability to manage the class on student learning outcomes in the field of PAI.